Respuesta :

A product of several terms equals zero. When a product of two or more terms equals zero, then at least one of the terms must be zero. We shall now solve each term = 0 separately. In other words, we are going to solve as many equations as there are terms in the product. Any solution of term = 0 solves product = 0 as well.

Solve  :    3x-1 = 0 
 
Add  1  to both sides of the equation : 
 
                     3x = 1 
Divide both sides of the equation by 3:
                     x = 1/3 = 0.333 

 Solve  :    x+4 = 0  Subtract  4  from both sides of the equation :                       x = -4 

x = -4 and x = 1/3 or 0.333

Answer:

Option (a) is correct.

The sum of roots of given quadratic equation [tex]-\frac{11}{3}[/tex]

Step-by-step explanation:

Given quadratic equation [tex]3x^2+11x+4=0[/tex]

We have to find the sum of roots.

Consider the given quadratic equation [tex]3x^2+11x+4=0[/tex]

For a given standard quadratic equation [tex]ax^2+bx+c=0[/tex] , we have

Sum of roots is given by [tex]-\frac{b}{a}[/tex]

and product of roots is given by [tex]\frac{c}{a}[/tex]

Thus, for the  given quadratic equation [tex]3x^2+11x+4=0[/tex]

a = 3 , b = 11 , c = 4

So, the sum of roots is given by [tex]-\frac{b}{a}[/tex]

Substitute, we get,

Thus, The sum of roots of given quadratic equation [tex]-\frac{11}{3}[/tex]